2019
DOI: 10.1111/1365-2435.13420
|View full text |Cite
|
Sign up to set email alerts
|

The response of root traits to precipitation change of herbaceous species in temperate steppes

Abstract: Plasticity of root traits plays an important role in plant growth and survival under changing climate. Shift in precipitation is one of the most pertinent global change factors driving changes in structure and function of grasslands. However, few studies have investigated intraspecific variation of root traits in response to precipitation change under field conditions. We conducted a 10‐year simulated increased precipitation experiment in a temperate grassland and a 700‐km regional scale transect along a preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 77 publications
3
39
1
Order By: Relevance
“…Thus, the apparent disadvantage of building an expensive root system with thicker roots under water‐limited conditions, may be further compensated by long‐lived roots (Kong et al., 2017; Weemstra et al., 2016). Our results support recent studies (Zhou et al., 2018; Zhou, Wang, Bai, Zhang, & Zhang, 2019) showing that plants under drought increase root diameter.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the apparent disadvantage of building an expensive root system with thicker roots under water‐limited conditions, may be further compensated by long‐lived roots (Kong et al., 2017; Weemstra et al., 2016). Our results support recent studies (Zhou et al., 2018; Zhou, Wang, Bai, Zhang, & Zhang, 2019) showing that plants under drought increase root diameter.…”
Section: Discussionsupporting
confidence: 92%
“…These different trait patterns could not be attributed to different growth forms, as has been observed elsewhere on root (Zhao et al., 2016) and leaf traits (Midolo et al., 2019), because in our study, root trait patterns were highly variable within growth forms, and overlapping between species of different growth forms (Figure S4). Prior studies also observed idiosyncratic patterns in leaf (Albert et al., 2010; Kichenin et al., 2013; Read et al., 2017) and root trait variation along various environmental gradients (Kumordzi et al., 2019; Roybal & Butterfield, 2019; Zhou et al., 2019) suggesting that idiosyncrasy in intraspecific trait patterns may be a widespread phenomenon. As the different degrees of, and patterns in intraspecific trait variation may be influenced by species' phylogenetic background (Kembel & Cahill, 2005), phylogeny may be relevant to account for in future work.…”
Section: Discussionmentioning
confidence: 90%
“…For example, the mean soil volumetric water contents during growing season were significantly enhanced by increased precipitation from 2005 to 2014 (Supporting Information Fig. S1), and a significant increase in soil nitrate (NO 3 − )‐N concentration by increased precipitation was detected (Zhou et al ., 2019). Detailed information on the water addition experiment was described in our previous study (Zhou et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…S1), and a significant increase in soil nitrate (NO 3 − )‐N concentration by increased precipitation was detected (Zhou et al ., 2019). Detailed information on the water addition experiment was described in our previous study (Zhou et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%